The Influence of Google Classroom-Based Online Learning and Digital Media Literacy on Student Learning Achievement in Office Administration Education, Stambuk 2018 - Sri Mutmainnah (Outline Journal of Education, 2022)
The purpose of this study was to find out whether there is an effect of online learning using the Google Classroom application and digital media literacy on the learning achievement of Stambuk 2018 office administration education students, Faculty of Economics. This type of research is ex post facto using a quantitative approach. The population is 59 students where the entire population is the sample. The data analysis techniques used in this study are Validity Test, Reliability Test, Normality Test, Linearity Test, Multicollinearity Test, T and F Test. The results of the t test calculation explain that there is an effect of online learning based on Google classroom on learning achievement. Then digital media literacy has a positive and significant effect on learning achievement.